How open are open cultural data? – Some critical remarks on an ongoing discussion - Koch, Gertraud (Hamburger Journal für Kulturanthropologie (HJK), 2018)
The following address was given as the opening reception by Prof. Dr. Gertraud Koch, University of Hamburg, at the “Sharing is Caring – Hamburg Extension” conference on collaboration in the GLAM sector (galleries, libraries, archives, museums), a joint event by the Museum für Kunst und Gewerbe Hamburg and the University of Hamburg, on April 20, 2017. For the video documentation see https://lecture2go.uni-hamburg.de/l2go/-/get/v/21392; for the conference’s closing statement and documentation see: http://sharecare.nu/hamburg-2017/